Optimizing Banking Operations Through Integrated Management Information Systems - Husna Anniyati (Academia Open, 2025)
Background (General): Management Information Systems (MIS) have become an essential component in modern organizations, particularly in the financial sector, where accurate and timely information is critical for decision-making and operational control. The banking industry, as one of the most data-driven sectors, relies heavily on MIS to ensure efficiency, security, and competitiveness. Background (Specific): In many banking institutions, challenges such as data redundancy, system inefficiency, and fragmented communication between departments still hinder optimal operations. These issues reduce productivity and limit the ability of banks to respond quickly to market dynamics and customer needs. Knowledge Gap: Although previous studies have highlighted the importance of information systems in banking, few have examined how MIS specifically contributes to integrating operational processes, improving managerial decision-making, and enhancing customer satisfaction within a dynamic digital environment. Aim: This study aims to analyze the role and impact of Management Information Systems in supporting operational effectiveness, improving coordination, and strengthening strategic management in banking operations. Results: The analysis reveals that effective implementation of MIS significantly improves operational accuracy, risk management, and service quality. Banks with well-integrated MIS systems demonstrate higher efficiency in transaction processing, faster decision-making, and greater transparency in financial reporting. Novelty: Unlike earlier studies that focus solely on technological aspects, this research emphasizes the holistic role of MIS in connecting human, technological, and managerial dimensions within banking institutions. Implications: The findings suggest that Management Information Systems serve as a vital foundation for banks to achieve sustainable performance and adaptability in the face of rapid digital transformation. Strengthening MIS infrastructure and human capacity can further enhance innovation and competitiveness in the banking industry. Highlights: MIS enhances operational efficiency and decision-making in banking. Integrated systems improve coordination, risk control, and service quality. Continuous investment in technology and human resources strengthens competitiveness. Keywords: Management Information Systems, Banking Operations, Efficiency, Decision-Making, Digital Transformation